2014
DOI: 10.1186/s12933-014-0110-2
|View full text |Cite
|
Sign up to set email alerts
|

DPP-4 inhibitor and alpha-glucosidase inhibitor equally improve endothelial function in patients with type 2 diabetes: EDGE study

Abstract: BackgroundAlpha glucosidase inhibitor (GI) attenuates postprandial hyperglycemia (PPH) and reduces the risk of cardiovascular events in patients with impaired glucose tolerance or type 2 diabetes. Dipeptidyl peptidase 4 (DPP-4) inhibitors also attenuate PPH. PPH is one of the factors leading to endothelial dysfunction which is an early event in the pathogenesis of atherosclerosis. Furthermore, DPP-4 inhibitors protect endothelial function through a GLP-1-dependent mechanism. However, the impact of these two ty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
101
3
3

Year Published

2015
2015
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 114 publications
(107 citation statements)
references
References 41 publications
0
101
3
3
Order By: Relevance
“…24 In comparison, a Japanese group found a significant improvement in flow-mediated vasodilation in patients treated with sitagliptin due to an increase in CD34 that is a marker of endothelial progenitor cells. 25 Hence, there is a lack of real clarity regarding the effects of DPP-4 inhibitors on endothelial function.…”
Section: Effects On Endothelial Functionmentioning
confidence: 99%
“…24 In comparison, a Japanese group found a significant improvement in flow-mediated vasodilation in patients treated with sitagliptin due to an increase in CD34 that is a marker of endothelial progenitor cells. 25 Hence, there is a lack of real clarity regarding the effects of DPP-4 inhibitors on endothelial function.…”
Section: Effects On Endothelial Functionmentioning
confidence: 99%
“…Two papers reported that sitagliptin and trelagliptin did not improve FMD or RH-PAT responses in patients with T2DM when given for three months 61,62) . However, sitagliptin, alogliptin, vildagliptin, and tenegliptin improved endothelial dysfunction in most studies [63][64][65][66][67] . We reported that long-term therapy with sitagliptin failed to improve FMD relative to conventional treatment 61) .…”
Section: In Vivo or Ex Vivo Experimentsmentioning
confidence: 93%
“…Adding sitagliptin to conventional antihyperglycemic drugs for two years in patients with T2DM did not alter endothelial function measured by FMD. Antihyperglycemic agents including metformin, pioglitazone, and an α-glucosidase inhibitor have been found to improve glycemic control in patients with T2DM 61,66,[68][69][70] . Based on lowering glucose levels with anti-diabetic drugs, reduction of hyperglycemia may improve endothelial dysfunction clinically.…”
Section: In Vivo or Ex Vivo Experimentsmentioning
confidence: 99%
“…Indeed, DPP-4 inhibitors have been shown to have anti-inflammatory and anti-atherogenic effects in an animal model [18][19][20]. In addition, DPP-4 inhibitors improve endothelial function [21,22], as well as attenuate neointima formation after vascular injury [23]. It has been speculated that lowering plasma glucose levels using DPP-4 inhibitors or GLP-1 receptor agonists could attenuate the progression of coronary atherosclerosis and lead to a better cardiovascular prognosis.…”
Section: Introductionmentioning
confidence: 99%